Formatio Keluarga Sebagai Upaya Menanggapi Fenomena Konversi Agama - Benedictus Hasan; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Jurnal Pelayanan Pastoral, 2021)
This paper focuses on elaboration on the phenomenon of religious conversion. This phenomenon on the one hand can be said to be an expression of religious freedom. Religious freedom itself is governed by the Constitution, the Declaration on Human Rights and some Church documents. However, on the other hand, conversion of religion can also be seen as weak militancy of the faith, which in this context is the catholic faith in the Catholic Church. In this paper, the author will put the assumption of the occurrence of this phenomenon of religious conversion in the second point, namely because of the weak militancy of faith. Therefore, this phenomenon must be found a solution as an effort to overcome it. The militancy of faith is very important in religious life, so this needs to be addressed. In writing this article, the author uses the library research method. The author conducted readings of several supporting sources and several Church documents as the main sources of this study. Then, the findings or commentary of this study is an effort to overcome the phenomenon of religious conversion can be overcome by conducting a catechism of family faith coaching, which focuses on the fides quae aspect of the life of the believer.